The Mystery behind Smoke and Its Addiction - Bhambhani, Garima; Saxena, Vrinda; Pandya, Poonam; Pandya, Nitin; Thakur, Bhanupriya; Ahuja, Rinky (Journal of Orofacial Research, 2015)
Smoking has addictive implication primarily due to tobacco. This addiction usually starts in the early teenage years and because of which many manifestations are seen. Nicotine has pervasive effects on brain, difficulty in cognitive processing and so many effects. Combination of the 4,000 or more chemical  components of tobacco smoke, including a huge arsenal of toxins and carcinogens, represent the mediators of multiple pathogenic processes. Nicotine has various delivery systems like cigarette, cigar and pipe and smokeless tobacco. At the time of quitting tobacco individual faces many withdrawal  symptoms due to craving. These withdrawal symptoms particularly irritability, restlessness, feeling miserable, impaired concentration, and increased appetite begin within hours of the last cigarette and are at maximal intensity for the first week. But social influences greatly influence addiction patterns. These can be used to discourage smoking. Successful interventions need to tackle the interacting constellation of factors—personal, family; socioeconomic, and pharmacological.